2017
DOI: 10.1016/s1473-3099(17)30117-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Third International Consensus Definitions for Sepsis (Sepsis-3) Classification: a retrospective population-based cohort study

Abstract: BACKGROUND The Third International Consensus Definitions for Sepsis (Sepsis-3) present clinical criteria for classifying infection patients. Event incidence and long-term outcomes across these classifications are unknown. METHODS We conducted a retrospective analysis using data from 30,239 US participants aged ≥45 years enrolled in the REasons for Geographic and Racial Differences in Stroke (REGARDS) cohort. We identified hospitalizations over 2003–2012 using three classifications: infection with systemic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
107
0
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 30 publications
7
107
0
6
Order By: Relevance
“…showed the SOFA was predictive of outcome in ED patients with borderline or confirmed septic shock . More recent retrospective studies using large cohorts have shown SOFA performed well in community stroke patients and using qSOFA in ED . Conversely, the SOFA score was very effective in identifying those with suspected sepsis in ED who had a low mortality risk (negative predictive value 97.9% for 30 day mortality).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…showed the SOFA was predictive of outcome in ED patients with borderline or confirmed septic shock . More recent retrospective studies using large cohorts have shown SOFA performed well in community stroke patients and using qSOFA in ED . Conversely, the SOFA score was very effective in identifying those with suspected sepsis in ED who had a low mortality risk (negative predictive value 97.9% for 30 day mortality).…”
Section: Discussionmentioning
confidence: 96%
“…SOFA has been most well known and applicable to the critical care community . As yet there have been relatively few reports of clinical use of the SOFA score in the ED setting, especially in undifferentiated patients with suspected sepsis . The quick SOFA (qSOFA) score is more readily applied in ED and experience with its use in the pre‐hospital setting is emerging, but qSOFA may be insufficiently sensitive, in particular because acute renal dysfunction that is common in sepsis is not included in qSOFA in contrast to the SOFA score …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the context of this epidemiologic study, the similar outcomes between qSOFA and non-qSOFA sepsis cases may actually be a strength, supporting the use of qSOFA as an additional strategy for identifying sepsis cases. We have previously illustrated the utility of qSOFA in characterizing community-acquired sepsis susceptibility and mortality (23). We note that ED Sepsis cases fulfilling both Original and qSOFA criteria exhibited higher rates of ICU admission than those with either criteria alone, suggesting synergy between the two classification approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In an examination of 2593 first infection events recorded in a large US database, 1526 met SIRS criteria, whereas criteria for SOFA and qSOFA were met by 1080 and 378, respectively, with corresponding mortality rates of 9%, 13%, and 23%, respectively [2].…”
mentioning
confidence: 99%